Simplified dolutegravir dosing for children with HIV weighing 20 kg or more: pharmacokinetic and safety substudies of the multicentre, randomised ODYSSEY trial. Issue 8 (August 2020) - Bollen, Pauline D J; Moore, Cecilia L; Mujuru, Hilda A; Makumbi, Shafic; Kekitiinwa, Adeodata R; Kaudha, Elisabeth; Parker, Anna; Musoro, Godfrey; Nanduudu, Annet; Lugemwa, Abbas; Amuge, Pauline; Hakim, James G; et al.
Summary: Background: Paediatric dolutegravir doses approved by stringent regulatory authorities (SRAs) for children weighing 20 kg to less than 40 kg until recently required 25 mg and 10 mg film-coated tablets. These tablets are not readily available in low-resource settings where the burden of HIV is highest. We did nested pharmacokinetic substudies in patients enrolled in the ODYSSEY-trial to evaluate simplified dosing in children with HIV. Methods: We did pharmacokinetic and safety substudies within the open-label, multicentre, randomised ODYSSEY trial (NCT02259127 ) of children with HIV starting treatment in four research centres in Uganda and Zimbabwe. Eligible children were randomised to dolutegravir in ODYSSEY and weighed 20 kg to less than 40 kg. In children weighing 20 kg to less than 25 kg, we assessed dolutegravir's pharmacokinetics in children given once daily 25 mg film-coated tablets (approved by the SRAs at the time of the study) in part one of the study, and 50 mg film-coated tablets (adult dose) or 30 mg dispersible tablets in part two of the study. In children weighing 25 kg to less than 40 kg, we also assessed dolutegravir pharmacokinetics within-subject on film-coated tablet doses of 25 mg or 35 mg once daily, which were approved by the SRAs for the children's weight band; then switched to 50 mg film-coated tablets once daily. Steady-state 24 h dolutegravir plasma concentration-time pharmacokinetic profiling was done in all enrolled children at baseline and 1, 2, 3, 4, 6, and 24 h after observed dolutegravir intake. Target dolutegravir trough concentrations (Ctrough ) were based on reference adult pharmacokinetic data and safety was evaluated in all children in the corresponding weight bands who consented to pharmacokinetic studies and received the studied doses. Findings: Between Sept 22, 2016, and May 31, 2018, we enrolled 62 black-African children aged from 6 years to younger than 18 years (84 pharmacokinetic-profiles). In children weighing 20 kg to less than 25 kg taking 25 mg film-coated tablets, the geometric mean (GM) Ctrough (coefficient of variation) was 0·32 mg/L (94%), which was 61% lower than the GM Ctrough of 0·83 mg/L (26%) in fasted adults on dolutegravir 50 mg once-daily; in children weighing 25 kg to less than 30 kg taking 25 mg film-coated tablets, the GM Ctrough was 0·39 mg/L (48%), which was 54% lower than the GM Ctrough in fasted adults; and in those 30 kg to less than 40 kg taking 35 mg film-coated tablets the GM Ctrough was 0·46 mg/L (63%), which was 45% lower than the GM Ctrough in fasted adults. On 50 mg film-coated tablets or 30 mg dispersible tablets, Ctrough was close to the adult reference (with similar estimates on the two formulations in children in the 20 to <25 kg weight band), with total exposure (area under the concentration-time curve from 0 h to 24 h) in between reference values in adults dosed once and twice daily, where safety data are reassuring, although maximum concentrations were higher in children weighing 20 kg to less than 25 kg than in the twice-daily adult reference. Over a 24-week follow-up period in 47 children on 30 mg dispersible tablets or 50 mg film-coated tablets, none of the three reported adverse events (cryptococcal meningitis, asymptomatic anaemia, and asymptomatic neutropenia) were considered related to dolutegravir. Interpretation: Adult dolutegravir 50 mg film-coated tablets given once daily provide appropriate pharmacokinetic profiles in children weighing 20 kg or more, with no safety signal, allowing simplified practical dosing and rapid access to dolutegravir. These results informed the WHO 2019 dolutegravir paediatric dosing guidelines and have led to US Food and Drug Administration approval of adult dosing down to 20 kg. Funding: Paediatric European Network for Treatment of AIDS Foundation, ViiV Healthcare, UK Medical Research Council.